Pengawasan Penangkapan Ikan di Zona Ekonomi Eksklusif Indonesia dalam Membangun Poros Maritim Indonesia - Ishak, Nurfaika; Fatimah, Siti (Wacana Hukum, 2019)
Abstract Indonesia is a maritime country that has an abundance of marine natural resources, especially fisheries resources. The wealth of Indonesian fisheries resources should be managed in such a way as to be able to provide benefits for the greatest prosperity of the people (in accordance with the mandate of the 1945 Constitution). Normatively, Law Number 31 Year 2004 which has changed with Law Number 45 of 2009 concerning Fisheries, has been regulated regarding the management of fisheries in Chapter XII Article 66-70. The urgency of supervision in the fisheries sector is intended so that all regulations can be implemented in accordance with what has been determined. But in reality there are so many deviations in the aspects of management and protection of fisheries resources especially in the fishing process. Crimes and violations that occur such as Illegal, Unreported, and Unregulated Fishing activities result in very large material losses reaching Rp.101,040 trillion / year. In addition to material losses, Indonesia also suffered other losses in the form of invaluable environmental damage to violations of sovereignty limits.  Abstrak Indonesia adalah negara maritim yang memiliki limpahan sumber daya alam kelautan khususnya sumber daya perikanan. Kekayaan sumber daya perikanan Indonesia seyogyanya dapat dikelola sedemikian rupa sehingga mampu memberikan manfaat bagi sebesar-besarnya kemakmuran rakyat (sesuai dengan amanat UUD Tahun 1945). Secara normatif, Undang-Undang Nomor 31 Tahun 2004 yang mengalami perubahan dengan Undang-Undang Nomor 45 Tahun 2009 tentang Perikanan, telah diatur mengenai pegawasan perikanan pada Bab XII Pasal 66-70. Urgensi adanya pengawasan pada bidang perikanan dimaksudkan agar seluruh peraturan dapat dilaksanakan sesuai dengan apa yang telah ditetapkan. Namun dalam kenyataannya ditemukan begitu banyak hal menyimpang dalam aspek pengelolaan dan perlindungan sumber daya perikanan terkhusus pada proses penangkapan ikan. Kejahatan dan pelanggaran yang terjadi seperti kegiatan Illegal, Unreported, and Unregulated Fishing mengakibatkan kerugian materil yang sangat besar hingga mencapai Rp.101.040 Trillin/Tahun. Selain kerugian materil, Indonesia juga mengalami kerugian lain berupa kerusakan lingkungan yang tak ternilai hingga pelanggaran terhadap batas kedaulatan.